Credit Shocks in the Financial Deregulatory Era: Not the Usual Suspects - Szilárd Benk; Max Gillman; Michal Kejak (Cardiff University, Cardiff Business School, 2005)
The paper constructs credit shocks using data and the solution to a monetary business cycle model. The model extends the standard stochastic cash-in-advance economy by including the production of credit that serves as an alternative to money in exchange. Shocks to goods productivity, money, and credit productivity are constructed robustly using the solution to the model and quarterly US data on key variables. The contribution of the credit shock to US GDP movements is found, and this is interpreted in terms of changes in banking legislation during the US financial deregulation era. The results put forth the credit shock as a candidate shock that matters in determining GDP, including in the sense of Uhlig (2003).
Keywords: E32; E44; 330; Business cycle; credit shocks; financial deregulation